The doll people - Martin, Ann M., 1955- (Martin, Ann M., 1955- Doll people story., 2000)
A family of porcelain dolls that has lived in the same house for one hundred years is taken aback when a new family of plastic dolls arrives and doesn't follow The Doll Code of Honor.